2004
DOI: 10.1097/01.tp.0000121763.44137.fa
|View full text |Cite
|
Sign up to set email alerts
|

Resource Use and Treatment Costs After Kidney Transplantation: Impact of Demographic Factors, Comorbidities, and Complications

Abstract: These results show that posttransplant clinical outcomes result in a significant increase in treatment costs. Because the economic impact of primary causes of chronic rejection (acute rejection and CMV) and delayed graft function is substantial, careful selection of the most appropriate immunosuppressive regimen is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 21 publications
2
38
1
1
Order By: Relevance
“…Further, these therapies are associated with a number of serious complications such as de novo malignancies, post-transplant diabetes, cardiovascular morbidity, and infections, which are both stressful and detrimental for an individual and costly with regard to the increasing health-care expenditure [13]. In summary, the role of immunosuppression for the success of transplantation is pivotal from the payers' and the patients' perspective alike.…”
Section: Introductionmentioning
confidence: 96%
“…Further, these therapies are associated with a number of serious complications such as de novo malignancies, post-transplant diabetes, cardiovascular morbidity, and infections, which are both stressful and detrimental for an individual and costly with regard to the increasing health-care expenditure [13]. In summary, the role of immunosuppression for the success of transplantation is pivotal from the payers' and the patients' perspective alike.…”
Section: Introductionmentioning
confidence: 96%
“…[42][43][44] We do not have that data field in our retrospective claims, which may influence comparison of medical utilization and costs. Specialty and retail cohorts were balanced for new users to therapy using transplant medication claims (4% and 3%, respectively) and number of patients with first transplant medication claims during days 1-90, 91-180, 181-270, and 271 onward during the index period, but ≥ 84% of patients were on medication at the beginning of the index period and potentially prior to the baseline period as well.…”
Section: ■■ Conclusionmentioning
confidence: 99%
“…However, there is no study directly comparing the economic point of view of all used strategies. Previous pharmacoeconomic analyses showed that CMV prophylaxis is a cost-effective intervention in either D+/R– (donor-positive/recipient-negative CMV serologic status pretransplant) or R+ recipients [11,12,19,20,21,22,23,24]. Schnitzler et al [24] performed retrospective analysis of Medicare costs during the first year after kidney transplantation considering sero pairing outcomes showing total payments of USD 24,269 in the D–/R–, USD 28,904 in the D+/R–, USD 28,823 in the D–/R+ and USD 29,997 in the D+/R+ group.…”
Section: Introductionmentioning
confidence: 99%